Understanding IoT Adoption in Botswana’s SMEs: A Research Onion Approach - Mphale, Ofaletse; Gorejena, Karikoga Norman; Nojila, Olebogeng Hellen (Universitas Bina Darma, 2024)
The advent of the Internet of Things (IoT) presents a transformative opportunity for Small and Medium-sized Enterprises (SMEs), unlocking their potential for enhanced operational efficiency, productivity, and data-driven decision-making. However, harnessing these benefits necessitates a rigorous and structured methodological approach. On the next hand, selecting an appropriate research methodology can be problematic, as it demands consideration of context-specific factors. This study addresses a significant gap by theoretically evaluating and proposing a suitable